Proceedings IECON '91: 1991 International Conference on Industrial Electronics, Control and Instrumentation
DOI: 10.1109/iecon.1991.239180
|View full text |Cite
|
Sign up to set email alerts
|

Application of H infinity control to motor speed control system

Abstract: Hwcontrol theory was applied to motor speed control system to get controller which acts effectively with control object including uncertainties. A mixed sensitivity Hw control problem was composed and solved. After that, numerical simulation were executed to confirm ability of the controller.Here. the part Khich consists of T L . BL and Tc in Fig. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The latter report concluded that fuzzy logic performs better than PID controllers, but they require several fuzzy algorithm rules, which are not easy to conceive. There have been many other control strategies for the speed control of DC motors, for example, the well-known sliding mode control theory was used in [5], the H ∞ -robust control was invoked in [6], the adaptive control point of view was conceived in [7], and machine learning techniques were used in [8]. Whatever the strategy, the implementation of nonlinear controllers requires the programming of complex mathematical formulas.…”
Section: Introductionmentioning
confidence: 99%
“…The latter report concluded that fuzzy logic performs better than PID controllers, but they require several fuzzy algorithm rules, which are not easy to conceive. There have been many other control strategies for the speed control of DC motors, for example, the well-known sliding mode control theory was used in [5], the H ∞ -robust control was invoked in [6], the adaptive control point of view was conceived in [7], and machine learning techniques were used in [8]. Whatever the strategy, the implementation of nonlinear controllers requires the programming of complex mathematical formulas.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, existing papers often deal with the robust control of speed and position loop with neglected electrical part of the motor [5], [6], [7]. There are also attempts to realize robust current control for PMS motors [8].…”
Section: Introductionmentioning
confidence: 99%